Some Characterization of Fuzzy Hazard Rate Order and Fuzzy Proportional Hazard Rate Order - D. Rajan; D. Vijayabalan (International Journal of Mathematics And its Applications, 2017)
In this paper, we have recalled some of the known stochastic orders and the shifted version of them, so discussed their relations. Also, we obtained some applications of proportional hazard rate ordering.